Microwave Active Devices and Circuits for Communication - Bera, Subhash Chandra (Lecture Notes in Electrical Engineering, 2019)
The book discusses active devices and circuits for microwave communications. It begins with the basics of device physics and then explores the design of microwave communication systems including analysis and the implementation of different circuits. In addition to classic topics in microwave active devices, such as p-i-n diodes, Schottky diodes, step recovery diodes, BJT, HBT, MESFET, HFET, and various microwave circuits like switch, phase shifter, attenuator, detector, amplifier, multiplier and mixer, the book also covers modern areas such as Class-F power amplifiers, direct frequency modulators, linearizers, and equalizers. Most of the examples are based on practical devices available in commercial markets and the circuits presented are operational. The book uses analytical methods to derive values of circuit components without the need for any circuit design tools, in order to explain the theory of the circuits. All the given analytical expressions are also cross verified using commercially available microwave circuit design tools, and each chapter includes relevant diagrams and solved problems. It is intended for scholars in the field of electronics and communication engineering.